2014
DOI: 10.1148/radiol.14140296
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy, Precision, and Reproducibility of Four T1 Mapping Sequences: A Head-to-Head Comparison of MOLLI, ShMOLLI, SASHA, and SAPPHIRE

Abstract: To compare accuracy, precision, and reproducibility of four commonly used myocardial T1 mapping sequences: modified Look-Locker inversion recovery (MOLLI), shortened MOLLI (ShMOLLI), saturation recovery single-shot acquisition (SASHA), and saturation pulse prepared heart rate independent inversion recovery (SAPPHIRE). Materials andMethods:This HIPAA-compliant study was approved by the institutional review board. All subjects provided written informed consent. Accuracy, precision, and reproducibility of the fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
258
2
4

Year Published

2015
2015
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 277 publications
(295 citation statements)
references
References 26 publications
31
258
2
4
Order By: Relevance
“…123,124 The most recently introduced approach is a combined IR-SR preparation scheme (Saturation pulse prepared heart rate-independent inversion recovery, SAPPHIRE). 125 In T1 or longitudinal magnetization, the magnitude is measured as a vector component in z direction (head-feet), whereas in T2 (discussed later), the vector component is measured in transverse or x-y plane. T1 accuracy of a sequence is defined by proximity/distance of a sequence-specific T1 value (T1 estimate) from the true T1 value, obtained by T1-TSE sequence.…”
Section: Basic Concepts Of T1 Mapping: From Acquisition To Postprocesmentioning
confidence: 99%
“…123,124 The most recently introduced approach is a combined IR-SR preparation scheme (Saturation pulse prepared heart rate-independent inversion recovery, SAPPHIRE). 125 In T1 or longitudinal magnetization, the magnitude is measured as a vector component in z direction (head-feet), whereas in T2 (discussed later), the vector component is measured in transverse or x-y plane. T1 accuracy of a sequence is defined by proximity/distance of a sequence-specific T1 value (T1 estimate) from the true T1 value, obtained by T1-TSE sequence.…”
Section: Basic Concepts Of T1 Mapping: From Acquisition To Postprocesmentioning
confidence: 99%
“…A technical review of the strengths and weaknesses of these techniques can be found elsewhere. 20 The Look-Locker technique and its modifications have higher reproducibility and precision, whereas SASHA and SAPPHIRE have improved accuracy. 20 In most of the published studies in CHD either the Look-Locker or MOLLI approach has been used.…”
Section: Cardiac Magnetic Resonancementioning
confidence: 99%
“…20 The Look-Locker technique and its modifications have higher reproducibility and precision, whereas SASHA and SAPPHIRE have improved accuracy. 20 In most of the published studies in CHD either the Look-Locker or MOLLI approach has been used. 21-24 Native T1 time refers to the T1 relaxation time without the administration of a gadolinium-based contrast agent.…”
Section: Cardiac Magnetic Resonancementioning
confidence: 99%
“…26 A recent comparison of the 4 most widely applied T1 mapping sequences demonstrated superior precision (ie, reproducibility) for the inversion recovery sequences MOLLI 20 and ShMOLLI, 22 while SASHA 24 and SAPPHIRE 26 were more accurate (ie, closer to the true T1). 27 The accuracy of the MOLLI sequence for postcontrast T1 times can be improved by using a different acquisition scheme which accounts for shorter T1 times. This scheme ensures that the majority of data points are positioned into the shortened upslope of the longitudinal relaxation curves of blood and myocardium.…”
Section: T1 Mapping In the Heartmentioning
confidence: 99%